2019
DOI: 10.1093/annonc/mdz059
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and total cancer incidence and mortality: a meta-analysis of randomized controlled trials

Abstract: Background: Previous meta-analyses of randomized controlled trials (RCTs) of vitamin D supplementation and total cancer incidence and mortality found inconsistent results, and most included trials administered generally low doses of vitamin D (1100 IU/day). We updated the meta-analysis by incorporating recent RCTs that have tested higher doses of vitamin D supplements.Materials and methods: PubMed and Embase were searched from the inception to November 2018. Summary relative risks (RRs) and 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
278
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(301 citation statements)
references
References 55 publications
11
278
1
11
Order By: Relevance
“…(45,46) Nevertheless, the protective benefit of vitamin D supplementation against cancer mortality became pronounced when pooling the large RCTs together. (9) In addition, two recent RCTs suggest that patients with digestive tract cancers, especially colorectal cancer, may benefit from vitamin D supplementation. (47,48) Our findings indicate that the assessment of vitamin D status using bioavailable instead of total 25OHD levels would aid in the identification of individuals who are most likely to benefit from vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(45,46) Nevertheless, the protective benefit of vitamin D supplementation against cancer mortality became pronounced when pooling the large RCTs together. (9) In addition, two recent RCTs suggest that patients with digestive tract cancers, especially colorectal cancer, may benefit from vitamin D supplementation. (47,48) Our findings indicate that the assessment of vitamin D status using bioavailable instead of total 25OHD levels would aid in the identification of individuals who are most likely to benefit from vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8) However, a recent meta-analysis of randomized controlled trials (RCTs) has demonstrated a divergent effect of vitamin D supplementation, which reduces total cancer mortality but does not lower total cancer incidence in the general population, supporting a broad benefit of vitamin D in cancer prognosis. (9) Consistent with this hypothesis, observational cohort studies have shown improved survival in cancer patients with higher circulating vitamin D concentrations, measured before or shortly after diagnosis of cancer. (10) However, evidence linking vitamin D status to organ-specific cancer survival is sparse and has produced conflicting results between and within types of cancers.…”
mentioning
confidence: 83%
“…Intake of ordinary doses of vitamin D supplements seems to be associated with decreases in total mortality rates [61]. A more recent 2019 study of higher dose random control trials showed that while vitamin D supplementation did not reduce total cancer incidence, it significantly reduced total cancer mortality [62]. There is evidence that critically ill patients with very low 25(OH)D concentrations have blunted responses to vitamin D replacement which may also explain the apparently negative results of earlier trials and meta-analyses [63].…”
Section: Causal Evidence For Vitamin Dmentioning
confidence: 99%
“…Vitamin D supplementation significantly reduced total cancer mortality but did not reduce total cancer incidence. 60 Patients with low-risk prostate cancer under active surveillance may benefit from vitamin D3 supplementation at 4000 IU/d. 61 Among patients with metastatic colorectal cancer, the addition of high-dose Vitamin D3, vs standard-dose Vitamin D3, to standard chemotherapy resulted in a difference in median progression-free survival that was not statistically significant, but with a significantly improved supportive effect.…”
Section: Discussionmentioning
confidence: 99%